Problem Kejahatan dan Kemahakuasaan Tuhan dalam Perspektif Advaita Vedanta: The Problem of Evil and the Omnipotence of God in the Perspective of Advaita Vedanta - Arta, I Gede Arya Juni (Undiksha, 2024)
This research examines the problem of evil and its relationship with the omnipotence of God from the perspective of Advaita Vedanta. Evil exists, and on the other hand, God also exists with various attributes of omnipotence, such as being all-perfect, all-good, all-powerful, and so on. This type of research is a literature study, using the hermeneutic method. The aim of this research is to conduct a philosophical study of the problem of evil and the relationship of God in the world. Based on the research findings, it is known that the world and its empirical phenomena are a projection of maya, and ignorance (avidya) is the cause of the duality of evil. Individuals who are enveloped in maya and avidya perceive this empirical world as real, whereas only Brahman is the ultimate reality. Sri Sankara asserts that the concept of a personal God (Saguna Brahman) is not the highest. The highest Brahman is Nirguna Brahman, an absolute reality without qualities, which is described through negation as neti-neti (not this, not that). The conflict in human understanding of a perfect God has created an imperfect world and the existence of evil in the face of a God with attributes of omnipotence, occurs at the level of limited human thinking. The limitations of the human mind in comprehending the unmanifested lead humans to only grasp a manifest God.